Anesteziološki pristop k politravmatizirancu s hudo poškodbo prsnega koša - Stopar Pintarič, Tatjana (Zdravniški vestnik, 2009)
Background One half of the trauma-caused death cases are of thoracic origin. In spite of their potentially life-threatening disposition, most thoracic injuries can be treated conservatively or by insertion of intercostal catheter. Only few patients require urgent thoracotomy within the reanimation procedure. The present case reports a politraumatised patient with a severe thoracic injury whose life was saved by an urgent thoracotomy. Conclusions Thedynamic nature of thoracic injuries requires continuous monitoring of the patient in order to observe and start treating any possibly dangerous conditions. The familiarity with the type, mechanism and pathophysiology of the injury, standardised diagnostic and therapeutic/reanimation procedures as well as operative and non-operative treatment methods, are all required for anoptimal treatment.
Keywords: Hematotoraks; Hemothorax; Multiple Trauma; Oživljanje; Pneumothorax; Pnevmotoraks; Politravma; poškodbe; prsni koš; Prsni koš, poškodbe; Rane nepenetrantne; Resuscitation; Thoracic Injuries; Thoracotomy; Torakotomija; Wounds, Nonpenetrating